2011
DOI: 10.4141/cjss10061
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium accumulation in wheat grain as affected by mineral N fertilizer and soil characteristics

Abstract: H. 2011. Cadmium accumulation in wheat grain as affected by mineral N fertilizer and soil characteristics. Can. J. Soil Sci. 91: 521Á531. Cadmium (Cd) is a heavy metal distributed in soil by natural processes and anthropogenic activities. It can accumulate in crops, such as spring milling wheat (Triticum aestivum L.), and its accumulation depends on crop species, soil factors, and agricultural practices like fertilizer inputs. Our objective was to study the effect of mineral N fertilizer and soil characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 44 publications
0
15
2
1
Order By: Relevance
“…The relationship was not improved using multiple linear regression with the inclusion of other factors such as the amount of irrigation applied to the site or grain yield. This is in contrast with several studies that have shown that N fertilizer application can increase Cd uptake in wheat grain (Wångstrand et al, 2007;Li et al, 2011), likely through soil acidification, changes in ion exchange, and plant physiological processes.…”
Section: Relationship Between Management Factors and Cadmium Concentrcontrasting
confidence: 99%
“…The relationship was not improved using multiple linear regression with the inclusion of other factors such as the amount of irrigation applied to the site or grain yield. This is in contrast with several studies that have shown that N fertilizer application can increase Cd uptake in wheat grain (Wångstrand et al, 2007;Li et al, 2011), likely through soil acidification, changes in ion exchange, and plant physiological processes.…”
Section: Relationship Between Management Factors and Cadmium Concentrcontrasting
confidence: 99%
“…The application of these fertilizers to the agricultural lands will lead to the accumulation of these metals in soil. Plants may absorb these metals when grown in contaminated soils (Chang et al 2014;Li et al 2011;Singh and Myhr 1998). …”
Section: Sources Of Metals In Aseer Fruits and Vegetablesmentioning
confidence: 99%
“…Uptake of Cd by wheat has been well documented, and variables controlling uptake are numerous (Gawalko et al, 2002;Franzen et al, 2006;Mitchell et al, 2000;Norvell et al, 2000;Weggler-Beaton et al, 2000;Wu et al, 2002). The main variables for increased Cd uptake are low soil pH and low soil organic matter, high soil Cd concentrations (Wu et al, 2002), N fertilizer applications (Li et al, 2011), and the presence of Cl salts (Norvell et al, 2000). The elevated Cd in the gypsum-treated plots may be a result of Cd being removed from the soil exchange sites by the oversaturation of Ca through gypsum applications.…”
Section: Wheat Yields and Grain Qualitymentioning
confidence: 99%